Optimasi Pengendalian Persediaan Bahan Kimia Dengan Pendekatan EOQ Menggunakan Algoritma Genetika - Dirce Maria Benevides; Evi Yiliawati (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2014)
Supply in a company asset that is idly invested. How to manage the inventory is the frequent issue arises so that every request can be served, with a minimum cost. PT.XYZ, is a provider of clean water. This research aims to control the supply of chemicals in the production process so that the total cost (TC) can be minimized. The research was conducted by using a multi-item Economic Order Quantity (EOQ). Furthermore, the system will be completed by Genetics Algorithm (GA) to acquire minimum TC of supply and an EOQ for each chemicals. The research outcome indicates that by applying GA the supply TC of Rp.3,995,584,171,8458 is acquired. This is lower comparing to the budget provided by the company i.e. Rp.6,443,800,000,0000. By optimizing, the supply TC can be saved up to 37.9%. The total order of each Chemical, is as follows: 24,875,9615 Kg, 18.8838 Kg, 72.7511 Kg and 452.9790 Kg.